Evaluasi Kesesuaian Spasial Peta Bahaya Tanah Longsor Weighted Overlay dan Peta InaRISK BNPB di Kabupaten Wonogiri - Aqiela Pradani Ulin Nuha; Yuli Priyana (Mataram University, 2026)
Wonogiri Regency recorded 992 landslide incidents from 2021 to 2025, but the availability of verified local-scale hazard maps is still limited. This study aims to analyze the differences in the area of hazard classes, the spatial suitability of high hazard classes, and the consistency level of both maps against sample points between the landslide hazard map based on the Weighted Overlay modeling and the BNPB InaRISK map in Wonogiri Regency. The Weighted Overlay method is constructed using four physical parameters, namely slope, rainfall, land use, and soil type, which are processed using ArcGIS Pro with the same resolution and scale. Spatial suitability is calculated based on the overlay of high hazard classes, while consistency with sample points is measured using Percentage Agreement at 50 sample points evenly distributed across 25 sub-districts. The results show that the Weighted Overlay map is dominated by the medium hazard class (176,658.12 ha) with full coverage and no NoData areas, whereas the BNPB InaRISK map is dominated by the high hazard class (46,306.08 ha) with several unclassified areas. The agreement of high hazard classes between the two maps only reaches 8.65%, with the highest agreement in Jatiroto District (21.45%) and the lowest in Wuryantoro (0.55%). The consistency level of both maps against sample points is 50%. The low spatial agreement indicates that the national-scale InaRISK BNPB map cannot be directly used as a reference for disaster mitigation at the district level without local adjustments.